In-channel managed aquifer recharge: a review of current development worldwide and future potential in Europe - Standen, Kathleen (2020)
Managed aquifer recharge (MAR) schemes often employ in-channel modifications to capture flow from ephemeral streams, and increase recharge to the underlying aquifer. This review collates data from 79 recharge dams across the world and presents a reanalysis of their properties and success factors, with the intent of assessing the potential of applying these techniques in Europe. This review also presents a narrative review of sand storage dams, and other in-channel modifications, such as natural flood management measures, which contribute to the retardation of the flow of flood water and enhance recharge. The review concludes that in-channelMARsolutions can increase water availability and improve groundwater quality to solve problems a ecting aquifers in hydraulic connection with temporary streams in Europe, based on experiences in other parts of the world. Therefore, to meet the requirements of the Water Framework Directive (WFD), in-channel MAR can be considered as a measure to mitigate groundwater problems including saline intrusion, remediating groundwater deficits, or solving aquifer water quality issues.